The more it changes, the more it is the same: an exploration of francophone African dictatorship novel (2011)
The Francophone African novel has been, since independence, a combative oeuvre. Despite the thematic and the aesthetic mutations that have characterized the evolution of this body of work, especially in the so-called postcolonial dispensation, the idea of the writer as “ecrivain engage” remains prevalent. This paper reveals that the oppressive boot (dictatorial regime) is neither black nor white. Drawing its substance from Patrick Ilboudo's Les Vertiges du trone, Ahmadou Kourouma’s En attendant le vote des betes sauvages and Mongo Beti’s Trov de soleil tue l’amour and Branle-bas en noir et blanc. these novels portray the banality of power, which has been the most confounding albatross of Francophone African countries since independence.